Place Branding Sumedang sebagai Puseur Budaya Sunda - Pramono, Anton; Hafiar, Hanny; Puspitasari, Lilis (Institut Hindu Dharma Denpasar, 2018)
The purpose of this study is to describe how Sumedang government build Sumedang as the center of Sundanese culture through Place Branding that includes the process of conducting SWOT analysis, Creating Brand Vision, Setting Program Goals and benchmarks, Implementing Brand Vision, and Brand Equity Evaluation. This research uses descriptive research method. Technique of collecting data of in-depth interview, observation and literature study. In this research concludes that: Sumedang government in conducting SWOT analysis there are room for improvement, in creating brand vision SPBS has taken into account the organization culture, identity, and government vision and mission but the brand vision are not articulated enough for the stakeholder as diferent meaning are comprehended, on setting program goals and benchmarks, the program goals are not articulated enough as the goals are to major and have no milestones which relatively easier to achieve, the benchmarks used by the government is also not detail enough which in return couldn’t give the governement best practices ideas for managing SPBS. In implementing brand vision, the government didn’t implement evaluation in order to response the distress in their internal body, on the external campaign program there are much area to be explored such as using PR surrogates as storyteller in telling the brand story and better management in social media., and then minimum qualifications for communcation staff of SPBS has to be made. Lastly, on brand equity evaluation there are room for improvement such as utilizing financial and consumer based evaluation to balance the image and substance of Place Branding.